The role of the vaginal microbiome in gynaecological cancer. (12th April 2017) - Champer, M; Wong, AM; Champer, J; Brito, IL; Messer, PW; Hou, JY; Wright, JD
Abstract : Human microbiome research has shown commensal bacteria to be a major factor in both wellness and disease pathogenesis. Interest in the microbiome has recently expanded beyond the gut to include a multitude of other organ systems for which the microbiome may have health implications. Here, we review the role of the vaginal microbiome in health and disease, with a particular focus on gynaecologic malignancies. Further, we suggest that it may be possible to expand the use of probiotics in the treatment of gynaecological cancers. Tweetable abstract: A review of the research to date on the relation between the vaginal microbiome and gynaecological cancers. Tweetable abstract: A review of the research to date on the relation between the vaginal microbiome and gynaecological cancers.